Developing reflective practice : Making sense of social work in a world of change - Atkinson, Michael; Martyn, Helen (Book collections on Project MUSE., 2000)
Developing reflective practice is an invaluable resource, employing a unique 'bottom-up' approach to learning. It presents vivid examples of social work practice with children and families, with real life illustrations of the dilemmas and challenges facing practitioners. With analytic commentaries at the end of each section, it provides essential guidance for students and sets standards for both training and practice.